HUMAN RESOURCE ACCOUNTING PRACTICES IN NEPALESE COMMERCIAL BANKS - Uday Kishor Tiwari; Alwiyah Alwiyah (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
This research aims to examine Human Resource Accounting Practices in Nepalese Commercial Banks. A descriptive design is utilized for this study. Human Resource Accounting Disclosure Index (HRADI) is applied, focusing on five main indicators: the nature of Human Resource Accounting (HRA), valuation of HRA, financial statements regarding HRA, auditing practices for HRA, and enhancement programs for HRA practices, as well as using the Lev and Schwartz Model to draw conclusions. The analysis considered all 20 commercial banks operating in Nepal as the population sample. To achieve the objectives of this research, both primary and secondary data are gathered. Primary data was collected through judgmental sampling, where selected respondents completed questionnaires, while secondary data was sourced from the annual reports of the banks. Among the 20 banks, only Standard Chartered Bank Nepal Limited (SCBNL) and Nabil Bank Limited (NBL) were included in the sample. Authorized human resource officers from these banks participated in the study. The analysis of the data utilized HRADI and the Lev and Schwartz model. Results indicated that HRADI for SCBNL and NBL were 69.23% and 76.92%, respectively, suggesting that human resource accounting practices at both banks have not reached satisfactory standards. Both institutions follow the Nepal Financial Reporting Standard, classifying human resource expenses under Personnel Expenses and Deferred Employee Expenditure, yet neither has established a true valuation for their human resources.